Elderly Healthy Living Culture Connection Withrheumatic Disease Preventio Efforts Inpelayanan Sosial Elderly And Childrenchildren Area Binjai And Medan - Chairunisa, Milna; Gultom, Heri (School of Nursing, Faculty of Medicine, Tanjungpura University, 2022)
Background: Rheumatic disease not only attacks the joints, but also attack organs or other body parts. According to WHO (World Health Organization) estimates that approximately 335 million people worldwide suffer from rheumatic diseases. This number corresponds with the increase of elderly man and a variety of other health factors that are predicted to continue to increase in the future. It is estimated that approximately 25% of patients with rheumatic will experience a disability due to damage to the bone and joint disorders. Objective: aims to determine the relationship of culture of healthy living elderly with Rheumatic disease prevention efforts in UPT social services elderly and young children Binjai